Dwelling in Architecture: Design for a House for Two Strangers - Hanlen, M A (Auckland University of Technology, 2007)
This exegesis seeks to explicate the current Masters project Dwelling in Architecture. The design component of the project a House for Two Strangers seeks to design a hypothetical domestic dwelling for two unrelated domestic strangers to inhabit. The site for the House for Two Strangers is located in Central Auckland City, on the corners of Beresford Square and Hopetoun Street. Dwelling in Architecture seeks to explore the possibility of engaging with notions of spatiality or temporality outside of homogeneous demarcation of space and time. Through the project a number of texts have been referred to in regard to questions concerning of the movement of subject-bodies through a spatio-temporal field. In conjunction to this questioning, has been a question concerning the locale of dwelling.
Keywords: Architectural concepts; Housing design; Spatial; Temporal